DEVELOPMENT OF INTERACTIVE E-MODULE ON COLLIGATIVE PROPERTIES OF SOLUTIONS USING SIGIL - Raviqa A.F Maisessa; Erviyenni Erviyenni; Susilawati Susilawati (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2021)
DEVELOPMENT OF INTERACTIVE E-MODULE ON COLLIGATIVE PROPERTIES OF SOLUTIONS USING SIGILAbstractThe role of technology in education is very important in helping to achieve learning goals, especially during a pandemic like now. This research aims to develop teaching materials in the form of an interactive electronic module or e-Module on the colligative properties of solutions using Sigil. The output of Sigil's products has an ePub format that is easily accessible both offline and online. This teaching material contains videos and animations to help visualize the concept. The research method used Research and Development by following the Plomp model. e-Module has been validated by 2 material experts and 2 media experts, and trials of users to teachers and students. The results showed that the interactive e-Module has a very valid value of 4 assessment substances in the form of material substance, learning design, display (visual communication) and software utilization with a percentage of scores of 96.15%, 96.88%, 93.75%, and 95.19% respectively. The test results of user response each obtained a score of 96.67% with a very interesting category.AbstrakPeranan teknologi dalam pendidikan sangat penting dalam membantu tercapainya tujuan pembelajaran, terlebih pada masa pandemi seperti sekarang. Penelitian ini bertujuan untuk mengembangkan bahan ajar dalam bentuk modul elektronik atau e-Module yang bersifat interaktif pada materi sifat koligatif larutan menggunakan Sigil. Luaran dari produk Sigil memiliki format ePub yang mudah diakses secara offline maupun online. Bahan ajar ini dilengkapi dengan video dan animasi untuk membantu memvisualisasi konsep. Metode penelitian yang digunakan adalah Research and Development dengan mengikuti model Plomp. e-Module yang dikembangkan telah divalidasi oleh 2 ahli materi dan 2 ahli media, serta uji coba terhadap pengguna, yaitu guru dan peserta didik. Hasil penelitian menunjukkan bahwa e-Module interaktif yang dikembangkan memenuhi kriteria sangat valid dari 4 substansi penilaian yaitu substansi materi, desain pembelajaran, tampilan (komunikasi visual) dan pemanfaatan software dengan persentase skor berturut-turut sebesar 96,15%, 96,88%, 93,75%, dan 95,19%. Hasil uji respon pengguna masing-masing diperoleh skor 96,67% dengan kategori sangat menarik.